2020
DOI: 10.1158/0008-5472.can-19-3268
|View full text |Cite
|
Sign up to set email alerts
|

CircFOXK2 Promotes Growth and Metastasis of Pancreatic Ductal Adenocarcinoma by Complexing with RNA-Binding Proteins and Sponging MiR-942

Abstract: The detailed biological functions of circular RNA (circRNA) are largely unexplored. Using circRNA sequencing, we identified 169 differentially expressed circRNA in pancreatic ductal adenocarcinoma (PDAC) cells compared with nontumor human pancreatic ductal epithelial cells. Among them, circFOXK2 was validated with significant upregulation in PDAC cells and 63% of primary tumors (53 of 84). circFOXK2 promoted cell growth, migration, and invasion and was involved in cell-cycle progression and apoptosis. circFOXK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 44 publications
0
92
0
Order By: Relevance
“…Many studies have demonstrated that circRNAs play regulatory roles via sponging miRNAs and binding proteins (15,16,22,23). To con rm whether circDLC1 serves as "miRNA sponges", RNA immunoprecipitation assays (RIP) were performed in SNU 449 and HCC-LM9 cells using a speci c antibody against argonaute 2 (AGO2).…”
Section: Circdlc1 Interacts With Rna-binding Protein Hurmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that circRNAs play regulatory roles via sponging miRNAs and binding proteins (15,16,22,23). To con rm whether circDLC1 serves as "miRNA sponges", RNA immunoprecipitation assays (RIP) were performed in SNU 449 and HCC-LM9 cells using a speci c antibody against argonaute 2 (AGO2).…”
Section: Circdlc1 Interacts With Rna-binding Protein Hurmentioning
confidence: 99%
“…Circular RNAs (circRNAs), known as covalently closed and single-stranded transcripts, have been proved to exist in many species (13). Recent studies have reported that circRNAs was aberrantly expressed in many types of cancer, such as HCC (14), gastric cancer (15), and pancreatic ductal adenocarcinoma (16). The main function of circRNAs in tumor is sponging microRNAs (miRNAs), encoding protein or binding protein (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to miRNA binding, some circRNAs have been found to bind to RNA binding proteins (RBPs) through specific binding sites [39][40][41][42][43]. The study by Dai et al [39] found that the RBP trinucleotide repeat-containing 6A could bind to the flanked intron region of circ0006916 and regulate its biogenesis.…”
Section: Protein Bindingmentioning
confidence: 99%
“…In addition, circRNAs can bind to proteins to form functional complexes. For example, circFOXK2 could interact with the Y Box binding protein 1 and heterogeneous nuclear ribonucleoprotein K to form a complex, which could enhance NUF2 and PDXK expression in PDAC [42]. Another study showed that circSamd4 could form a complex with PUR proteins to enhance myogenesis through the suppression of myosin heavy chain transcription [43].…”
Section: Protein Bindingmentioning
confidence: 99%